(untitled) (Journal of Pathology of Nepal, 2024)
Background: Palpable breast lump is a common clinical presentation, and about 10% of them turn out to be breast cancer. The triple diagnostic approach - clinical examination, mammography, and cytology assists in diagnosing and determining the need for histopathological confirmation. The present study aims to compare mammography and cytology against the histopathological diagnosis to determine the sensitivity, specificity, negative predictive value, positive predictive value, and diagnostic accuracy of both techniques. Materials and Methods: This cross-sectional study, done from February 2023 to November 2024 included 50 patients presenting with a breast lump who underwent mammography, fine needle aspiration cytology (FNAC), and histopathological examination of the lump. Data were analyzed using SPSS software Ver.20, employing both descriptive and inferential statistics. Results: Out of 50 cases, 70%(35) were benign and 30%(15) were malignant. Fibroadenoma was the most common benign lesion 40%(20/50), while invasive ductal carcinoma was the most common malignant lesion 20%(10/50). Three-fourths of the benign cases occurred in patients under 45 years, while two-thirds of the malignant cases were in patients over 45. Mammography showed 60% sensitivity, 82.86% specificity, 60% positive predictive value (PPV), 82.86% negative predictive value (NPV), and diagnostic accuracy of 76%. FNAC showed 73.33% sensitivity, 97.14% specificity, 91.67% PPV, 89.47% NPV and diagnostic accuracy of 90%. Conclusions: Mammography and FNAC, when used together, supplement histopathological examination. FNAC offers higher accuracy than mammography and closely approximates histopathology in diagnosing breast lesions.